Online monitoring and collaborative scheduling method for wheelset cyber-physical production system: A wheelset manufacturing system case study from a Chinese high-speed train enterprise. (January 2021) - Bo, Hongguang; Han, Peng; Lu, Bo; Zhao, Can; Wang, Xingmian
Abstract: This paper proposes a quick response collaborative scheduling model based on Cyber-Physical Production System (CPPS) online monitoring to address the problem of quick response repair of disruption in the wheelset manufacturing of high-speed train. A Bogie Wheelset Manufacturing System-Quick response collaboration model (WS-QRC) that integrates disruption management and collaborative scheduling is established. An Enhance Neighborhood-Discrete Particle Swarm Optimization (DPSO_ENS) algorithm with extended neighborhood search structure is also designed. We take the data of a high-speed train factory in China as an example to verify the feasibility and superiority of the model and algorithm in this paper. Experimental examples have shown the supplier-led negotiation scheduling model and the improved DPSO algorithm are effective in dealing with the disruption and quick response problem during wheelset production.